Strategi Kreatif Iklan dan Brand Image Produk Minuman Happy Lemon di Instagram - Tanudjaya, Clarissa Karen; Sukendro, Gregorius Genep (Prologia, 2022)
Happy Lemon is a large beverage company that is growing and originating from Taiwan. It is essential for each company to introduce their products through an advertisement. In an advertisement besides having to have informative value, the advertisement must also have an interest for every individual who sees it, then a creative strategy will be needed in the formation of an advertisement. The design of creative strategies in the formation of advertisements is the main thing that needs to be achieved. The purpose of this observe is to give an explanation for how creative strategies are carried out in forming an advertisement on Instagram social media that can affect brand image. The researcher uses a qualitative research approach with qualitative descriptive methods. Data from the research results were obtained through commentary, interviews, and literature take a lool at. The consequences confirmed that Happy Lemon used a creative strategy in the formation of its advertisements on Instagram. One of the creative advertising strategies carried out by Happy Lemon is a creative message strategy, Happy Lemon packs messages in advertisements by holding Giveaway activities in their advertisements. Happy Lemon adalah perusahaan minuman besar yang berkembang serta berasal dari Taiwan. Setiap perusahaan penting untuk melakukan pengenalan produknya melalui sebuah iklan. Dalam sebuah iklan selain harus memiliki nilai yang informatif, iklan juga wajib memiliki ketertarikan bagi setiap individu yang melihatnya, maka strategi kreatif akan diperlukan dalam pembentukan sebuah iklan. Perancangan strategi kreatif dalam pembentukan iklan menjadi hal utama yang perlu untuk dilakukan. Penelitian ini bertujuam mengungkapkan bagaimana strategi kreatif yang perlu untuk dilakukan dalam membentuk sebuah iklan di media sosial Instagram yang dapat berpengaruh terhadap brand image. Peneiliti memakai pendekatan penelitian kualitatif dan menggunakan metode deskriptif kualitatif. Data dari hasil penelitian diperoleh melalui studi pustaka, wawancara, dan observasi. Hasil dalam penelitian ini menunjukkan bahwa Happy Lemon menggunakan strategi kreatif dalam pembentukan iklannya di Instagram. Salah satu strategi kreatif iklan yang dilakukan oleh Happy Lemon adalah strategi kreatif pesan, Happy Lemon mengemas pesan dalam iklan  dengan mengadakan kegiatan giveaway dalam iklannya.